(untitled) (Global Journal of Medical Research, 2021)
Coexistence of upper and lower respiratory diseases has long been known. Since chronic rhinosinusitis and pulmonary diseases are closely related this study was made to observe the pulmonary function of patients with chronic rhinosinusitis. Methods: The study was conducted in the Department of ENT and Pulmonary Medicine, IGMC Shimla on 27 adult patients of chronic rhinosinusitis and 26 age matched healthy control subjects between November 2018 and November 2019. The pulmonary function tests were performed using a spirometry and included Vital Capacity (VC) , Forced vital capacity (FVC) , Forced expiratory volume in one second (FEV1) and Forced expiratory volume in one second by Forced vital capacity ratio (FEV1/FVC). Results: Following observations were made from the results of the study, among controls majority of the subjects i.e 23 (92%) had a normal PFT with only 1 patient (4%) had mild and another 1 patient (4%) had moderate restriction on PFT. Whereas among the patients group 10 patients (37%) had a normal pre-operative baseline PFT. Another 10 (37%) and 7 patients (25.9%) had mild and moderate obstruction respectively.